The Relevance of Islamic Character Education According “The 7 Habits of Highly Effective People” Book - Siregar, Amy Fitriani; Asyiaty, Ismi Laela; Agustin, Bustanil Ilmi; Hidayat, Nur; Himam, Alin Safaraz (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to explore the relevance between the Islamic teachings on character education and the principles put forward by Stephen R. Covey in his book